Service Oriented Computing and Applications - Lin, Kwei-Jay.; Chung, Jen-Yao.; Chao, Kuo-Ming.; SpringerLink (Online service) (London : Springer London : Imprint: Springer.)
The aim of Service-Oriented Computing & Applications is to publish original and high quality research results on the service-oriented computing (SOC) paradigm, models and technologies that have significant contributions to the advancement of service oriented systems and their applications. Service-oriented computing has emerged as a major research topic in the past few years. Although the concept has evolved from earlier component-based software frameworks, web service standards are based on the readily and openly available internet protocols, and thus are easier and cheaper for companies to adopt. The strong support from major computer and IT service companies further speeds up the acceptance and adoption of SOC. However, service developers and users face many significant challenges and opportunities that are introduced by the dynamism of software service environments and requirements. This requires new concepts, methods, models, and technologies along with flexible and adaptive infrastructure for services developments and management in order to facilitate the on-demand integration and formation of services across different platforms and organizations. The success of service-oriented systems relies on the adoption of the derived technologies to meet the demands from the evolving environment. The journal focuses on the issues and research results related to the development of service-oriented technology, including service infrastructures, theoretical foundations and their applications and experiences in service-oriented computing. Topics covered by the journal include, but are not limited to, the following subjects as they relate to service-oriented computing and applications: Service-Oriented Architecture Services analysis, design, development and test Service orchestration and composition Resource management for web services Quality and reliability of web services Service-Oriented Software Engineering Formal methods for services analysis, design, development, and test Service requirement engineering SOA solution patterns Services matching and policy Verification and validation of SOA systems Quality and reliability of web services System Technology Security, trust and privacy QoS and end-to-end performance Web service standards Autonomic computing IP and digital right management Brokering and integration Service connection technology Grid-based web services Business Services and Technology Business service representation and knowledge Business process integration and management Supply chain and channel management Auction Negotiation E-business standards Service-Oriented Semantic Computing Semantic web Software agent Service discovery Ontological engineering Service evolutionary approaches Service-Oriented Applications E-business and e-commerce M-commerce E-entertainment E-learning E-government E-health.
Keywords: Information technology; Business -- Data processing; Computer organization; Software engineering; Application software; Management information systems; Computer science; E-commerce.; Computer Systems Organization and Communication Networks; Software Engineering/Programming and Operating Systems; e-Commerce/e-business.; Computer Appl. in Administrative Data Processing; Management of Computing and Information Systems; IT in Business